Digitalisasi manajemen strategi bank syariah dalam meningkatkan kepuasan nasabah - Pardi, Fira Meilinda (Maliki Interdisciplinary Journal, 2025)
The digitalization of strategic management in Islamic banks is a crucial step in addressing industry competition and meeting customer expectations. The adoption of digital technology enhances operational efficiency and service accessibility, but it must align with Sharia principles such as the prohibition of riba (interest), gharar (uncertainty), and maysir (speculation). This study aims to analyze the implementation of digitalization, its impact on customer satisfaction, and the challenges Islamic banks face in the digital transformation process. The findings reveal that digitalization plays a significant role in improving customer experience and satisfaction. However, Islamic banks encounter challenges in maintaining Sharia integrity and fulfilling technological demands in the digital era. Thus, effective strategic management and customer education are essential for the successful digitalization of Islamic banks.